Model Konstitutif Modulus Kekakuan Resilien Cement Treated Asphalt Mixture - R. Anwar Yamin (Direktorat Bina Teknik Jalan dan Jembatan, 2005)
Design thickness of pavement by mechanistic method may allow use of many types of pavement materials. Cement Treated Asphalt Mixture (CTAM) is one type of pavement surfacing layer which is a composite mixture consist of aggregates, asphalt and mortar cement. CTAM made from open graded and mortar cement as air void grouting agent resulted a new type of asphaltic mixture with a unique characteristic. So far, use of CTAM is not too popular since its chart or constitutive model for determination of its stiffness modulus is not available yet. The aim of this study was to formulate the constitutive models of stiffness modulus of CTAM (SCTAM). For meet this purpose, a laboratory experiment using CTAM made by varied types of asphalt; petroleum asphalt Pen 60 (AM), AM plus 3% latex type KKK-60 and AM plus Asbuton type of Retona-60 by ratio 4 : 1 (AA), three different of compressive strength of mortar cement. This test was conducted in elastic range of CTAM on three different temperatures. Constitutive models of SCTAM was formulate as a function of its affecting factor i.e. stiffness modulus of asphalt (Sbit), compressive strength of mortar (K), asphalt content (KA), void in mix of CTAM (VIMCTAM), void filled by mortar (VFMCTAM) and temperature (T). By use of 681 data, a quite feasible constitutive models SCTAM was derived